2012
DOI: 10.1038/emboj.2012.286
|View full text |Cite
|
Sign up to set email alerts
|

Wig1 prevents cellular senescence by regulating p21 mRNA decay through control of RISC recruitment

Abstract: Premature senescence, a key strategy used to suppress carcinogenesis, can be driven by p53/p21 proteins in response to various stresses. Here, we demonstrate that Wig1 plays a critical role in this process through regulation of p21 mRNA stability. Wig1 controls the association of Argonaute2 (Ago2), a central component of the RNA-induced silencing complex (RISC), with target p21 mRNA via binding of the stem-loop structure near the microRNA (miRNA) target site. Depletion of Wig1 prohibited miRNA-mediated p21 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 52 publications
(71 reference statements)
1
37
0
Order By: Relevance
“…Blockade of ERN1 in glioma cells also leads to the decreased expression of ZMAT3 (TP53 target zinc finger protein) gene but molecular mechanisms of this relation is not yet clear. There is data that ZMAT3 participates in the TP53-dependent growth regulatory pathway by regulation of TP53 expression and translocation to the nucleus as well as RNA-mediated gene silencing [26,28,35]. At the same time, recently was shown that ZMAT3 as an mRNA stabilityregulating protein prevents cellular senescence [28] and its decrease possibly participate in suppression of ERN1 knockdown of glioma cells proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockade of ERN1 in glioma cells also leads to the decreased expression of ZMAT3 (TP53 target zinc finger protein) gene but molecular mechanisms of this relation is not yet clear. There is data that ZMAT3 participates in the TP53-dependent growth regulatory pathway by regulation of TP53 expression and translocation to the nucleus as well as RNA-mediated gene silencing [26,28,35]. At the same time, recently was shown that ZMAT3 as an mRNA stabilityregulating protein prevents cellular senescence [28] and its decrease possibly participate in suppression of ERN1 knockdown of glioma cells proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SESN proteins provide an important link between genotoxic stress, TP53 and the mTOR signaling pathway. Recently was shown that ZMAT3 is an mRNA stability-regulating protein which prevents cellular senescence by regulating p21 mRNA decay through control of RISC recruitment [28]. ZMAT3 can bind different types of double-stranded RNAs, including small interfering RNAs and microRNAs [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Xenograft mice were established as described previously. 72 In brief, a single-cell suspension of H460 cells (1 × 10 6 ) was injected subcutaneously into the lateral hind leg of 6-week-old BALB/c nude mice (n = 5). Average tumor volume was determined as (L × W 2 )/2; measurements of tumor length (L) and width (W) were taken with a caliper.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of investigations into 3 ′ -UTR-mediated regulation has focused on isolated, individual elements within a 3 ′ UTR and have not determined how collections of elements might interact with one another. However, there exist a handful of examples of 3 ′ UTRs containing combinations of cis-regulatory elements that function cooperatively: Closely spaced binding sites for miRNAs can function synergistically, enhancing their regulatory impact (Grimson et al 2007;Saetrom et al 2007;Broderick et al 2011), and the binding of RBPs has been reported to both activate adjacent cryptic miRNA binding sites (Kim et al 2009(Kim et al , 2012Kedde et al 2010;Miles et al 2012) and mask otherwise functional sites (Bhattacharyya et al 2006;Kedde et al 2007;Léveillé et al 2011;Kundu, et al 2012). For example, two studies demonstrated that the binding of human Pumilio proteins within a 3 ′ UTR can induce a conformational change in the RNA structure.…”
Section: Introductionmentioning
confidence: 99%